The Importance Of Local Government Representative Bodies In Uzbekistan - Rametullaev Inayatulla Xabibullaevich (Research Parks Publishing LLC, 2021)
This article describes the council of people's deputies, which is a representative body of local government, their powers, importance, organizational form, it’s some activity principles.